1999
DOI: 10.1074/jbc.274.39.27536
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reagents and Divalent Cations Alter the Kinetics of Cystic Fibrosis Transmembrane Conductance Regulator Channel Gating

Abstract: Gating of the cystic fibrosis Cl؊ channel requires hydrolysis of ATP by its nucleotide binding folds, but how this process controls the kinetics of channel gating is poorly understood. In the present work we show that the kinetics of channel gating and presumably the rate of ATP hydrolysis depends on the species of divalent cation present and the oxidation state of the protein.With Ca 2؉ as the dominant divalent cation instead of Mg 2؉ , the open burst duration of the channel is increased approximately 20-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…4) or the wild type channel. (Gating of wild type CFTR can be affected by DTT at millimolar concentrations of this reducing agent (19).) Thus, the simplest explanation of our data is that the MTS reagents affected CFTR gating by forming mixed disulfides with the engineered cysteines at positions 54 and 58 in the CFTR amino-terminal tail.…”
Section: Covalent Modification Of the Double Cysteine Mutant Alters Amentioning
confidence: 68%
See 1 more Smart Citation
“…4) or the wild type channel. (Gating of wild type CFTR can be affected by DTT at millimolar concentrations of this reducing agent (19).) Thus, the simplest explanation of our data is that the MTS reagents affected CFTR gating by forming mixed disulfides with the engineered cysteines at positions 54 and 58 in the CFTR amino-terminal tail.…”
Section: Covalent Modification Of the Double Cysteine Mutant Alters Amentioning
confidence: 68%
“…In addition, since cysteines can be modified with methanethiosulfonate (MTS) derivatives with different chemistries (16), such experiments have the potential to provide initial insights into the structural requirements for the involvement of the N-tail in channel gating. We were encouraged to attempt this approach because of reports that the CFTR channel is relatively insensitive to low concentrations of thiol-specific reagents (17)(18)(19). Our results indicate that modification of these cysteines with either uncharged or charged MTS reagents markedly and reversibly reduces channel opening rate in excised membrane patches.…”
mentioning
confidence: 90%
“…In the experiment shown in A, unmodified subunit c accounts for 12% of the total subunit c in the experiment shown. channels and in the cystic fibrosis transmembrane conductance regulator (35,36). Cd 2ϩ has an ionic radius similar to that of Ag ϩ (0.95 and 1.15 Å, respectively), and Cd 2ϩ , like Ag ϩ , is a soft Lewis acid that forms a covalent bond with the thiolate form of cysteine (37).…”
Section: Resultsmentioning
confidence: 99%
“…Second, vitamin C is well known for its properties as an antioxidant, and we considered the notion that ascorbate activated CFTR directly by modifying its redox state. Previous work has shown that redox reagents alter the kinetics of CFTR gating such that reducing conditions (e.g., 2-mercaptoethanol and dithiotreitol) speed up gating and increase the open probability of CFTR (45), whereas oxidizing conditions slow gating of CFTR, presumably through cysteine residues present in the nucleotide-binding domains of CFTR (46). A variety of reducing and sulfhydryl-modifying agents activate CFTR in a similar manner.…”
Section: Discussionmentioning
confidence: 99%